Nutrition and Metabolic Adaptations in Physiological and Complicated Pregnancy: Focus on Obesity and Gestational Diabetes - Parrettini, Sara; Caroli, Antonella; Torlone, Elisabetta (Frontiers in Endocrinology, 2020)
Pregnancy offers a window of opportunities to program the future health of both mothers and offspring. During the gestational period, a woman experiences a series of physical and metabolic modifications and adaptations, which aim to protect the fetus development. Moreover, the pregnancy shows extreme flexibility of energy metabolism, which is closely related to both pre-gestational nutritional status and gestational weight gain. Recent evidence has highlighted the determinant role of nutritional status and maternal diet on both pregnancy outcomes and long-term risk of chronic diseases, through a transgenerational flow that found expression in the Development Origin of Health and Diseases (Dohad) theory. Therefore, the increased prevalence of pregnancies complicated by pregestational obesity and Gestational Diabetes should require greater attention, with a tailored metabolic and nutritional management which must ideally start in the pre-conceptional period and include the provision of strategies for the future health. Here, we will review the metabolic and endocrine adaptations that occur throughout pregnancy, as of anatomical and functional knowledge of the placental-fetal unit, and how these features impact on both maternal body composition and fetal development. Pre-gestational obesity represents a challenge of treatment, and nowadays its management makes use of new evidences, especially regarding the adequate weight gain. Nutritional recommendations and the use of nutraceuticals in pregnancy will be reviewed, with a focus on the management of pregnancy complicated by obesity and hyperglycemia. Finally, we will focus on the most recent evidence about the effects of ante-natal nutrition on the long-term, on either maternal health or metabolic risk of the offspring.